Enzymes Inhibition and Antidiabetic Effect of Isolated Constituents from Callistemon lanceoalatus - Kumar, Sunil; Kumar, Vipin; Prakash, Om; Ali, Mohammed (Natural Products Journal, The, 2013)
The present study was performed to investigate the enzyme inhibitory and antidiabetic activities of the constituents isolated from Callistemon lanceolatus. The leaves of C. lanceolatus were extracted with successively with petroleum ether, dichloromethane and methanol. The dried dichloromethane and methanol extracts were subjected to fractionation and chromatographic separation, which led to the isolation of seven compounds: 3-epi-betulinic acid (1), 3- epi-ursolic acid (2), oleanolic acid (3), ursolic acid (4), lup-12, 20(29)-diene-3α-ol-28-oic acid (5), heptacosenone (6) and kaempferol (7). Their structures were elucidated on the basis of spectroscopic studies as well as by comparison with the data available in the literature. Among these isolates, compounds 1, 2, 3, 4 and 7 were evaluated for in vitro enzyme inhibition effect. Compounds 1, 2, 3, 4 and 7 showed 38.34, 52.59, 62.4, 54.95 and 32.43 % α-amylase inhibition respectively and 49.27, 53.34, 84.2, 67.98 and 52.25 % α-glucosidase inhibition respectively at the concentration of 50 μg/kg. Compounds 3, 4 and 7 were also showed antidiabetic activity in streptozotocin-nicotinamide induced diabetic mice at the dose of 10 mg/kg.
Keywords: antidiabetic